Vaccination – an administrative social obligation - Ilieva, Reneta (Law Journal of New Bulgarian University, 2022)
The article examines the emergence of compulsory vaccination from a historical perspective. It distinguishes between recommended and compulsory vaccination. It discusses in detail the administrative legislation that provides for compulsory vaccination.